PEMBERDAYAAN PANDE BESI MELALUI PELATIHAN PRODUKSI BERKUALITAS DAN PEMASARAN DIGITAL PISAU DAN GOLOK DI BANJAR GERIH ABIANSEMAL BADUNG - I Made Darmada; I Komang Sukendra; Ni Luh Putu Tejawati; Dewa Ayu Widiasri (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2025)
Blacksmiths play an important role in providing metal-based tools for the community, particularly knives and machetes. However, blacksmiths in Banjar Gerih, Abiansemal Village, Badung Regency still face several problems in both production and marketing aspects, including limited access to high-quality raw materials, low production efficiency, and conventional marketing practices. This Community Service Program (PKM) aims to empower blacksmiths through training on quality production and digital marketing in order to improve product quality and expand market reach. The implementation method consisted of several stages, namely program socialization, production technique training, application of appropriate technology, digital marketing training, as well as continuous assistance and evaluation. The results show a significant improvement in the quality of knives and machetes in terms of sharpness, strength, and finishing neatness, along with increased production efficiency. In the marketing aspect, partners were able to utilize social media and marketplace platforms for product promotion and apply simple packaging and branding that increased product selling value. This program has proven to be effective in enhancing production capacity, expanding market reach, and positively impacting the partners’ income. Therefore, this PKM activity effectively improves the competitiveness and sustainability of blacksmith businesses in Banjar Gerih.